The evolvement of numeracy and mathematical literacy curricula and the construction of hierarchies of numerate or mathematically literate subjects - Jablonka, Eva (ZDM, 2015)
This contribution briefly sketches the evolvement of numeracy or mathematical literacy as models for mathematics curricula, which will be described as driven by a weakening of the insulation between discourses, that is, as a process of ‘declassification’. The question then arises as to whether and how coherence of new forms of initially heterogeneous sets of less specialised discourses is constituted through different ideological underpinnings. Differences in these underpinnings will be elaborated in order to allude to resulting tensions between the associated goals. As a weakening of classification creates less specialized discourses and identities, another issue pertains to how numeracy or mathematical literacy skills are translated into hierarchies of numerate or mathematically literate subjects. A selection of documents from national and supranational organisations will be used to illustrate what attributes of the test-takers become candidates for what labels and how numeracy or mathematical literacy ‘levels’ are constructed.